Predicting how climate change threatens the prey base of Arctic marine predators - Katie R. N. Florko; Travis C. Tai; William W. L. Cheung; Steven H. Ferguson; U. Rashid Sumaila; David J. Yurkowski; Marie Auger‐Méthé (Ecology Letters, 2021)
Arctic sea ice loss has direct consequences for predators. Climate‐driven distribution shifts of native and invasive prey species may exacerbate these consequences. We assessed potential changes by modelling the prey base of a widely distributed Arctic predator (ringed seal; Pusa hispida ) in a sentinel area for change (Hudson Bay) under high‐ and low‐greenhouse gas emission scenarios from 1950 to 2100. All changes were relatively negligible under the low‐emission scenario, but under the high‐emission scenario, we projected a 50% decline in the abundance of the well‐distributed, ice‐adapted and energy‐rich Arctic cod ( Boreogadus saida ) and an increase in the abundance of smaller temperate‐associated fish in southern and coastal areas. Furthermore, our model predicted that all fish species declined in mean body size, but a 29% increase in total prey biomass. Declines in energy‐rich prey and restrictions in their spatial range are likely to have cascading effects on Arctic predators.